14-3-3γ silencing impairs osteogenic differentiation of human adipose derived-mesenchymal stem cells - Rivera, Lautaro (2021)
14-3-3proteins constitute a family of regulatory molecules that participatein a plethora of cellular processes mainly through protein-proteininteractions. Even though 14-3-3 protein family members show somefunctional redundancy, there is growing evidence that indicatesevolutionary and biochemical diversity. Consistent with theliterature, previous research from our laboratory showed thatexpression levels of 14-3-3 paralogs are independently regulatedduring the adipogenesis and osteogenesis of human adiposederived-mesenchymal stem cells (hASCs). In the current work, we useda validated approach to isolate hASCs and studied the implication of14-3-3γon the osteogenic commitment of these cells. To address this purpose,we delivered a 14-3-3γshRNA construct into hASCs by pAd-BLOCKiT, an adenoviral vectorcontaining a human U6 promoter, and examined the effect on thedifferentiation potential into osteoblasts. The latter was evaluatedby: i) measuring alkaline phosphatase (ALP) activity, an early-stageosteoblast differentiation biomarker, and ii) detectingRunt-related transcription factor 2 (Runx2, master regulator of boneformation) protein levels. Cells were either maintained for 14 dayswith standard growth media (control, low glucose DMEM; 5% FBS) orinduced with an osteogenic differentiation medium (ODM; an optimizeddrug cocktail that includes dexamethasone, β-glycerophosphate,and 2-phospho-L-ascorbic acid). Our results clearly showed a decreasein both Runx2 protein levels and ALP activity in 14-3-3γdepleted hASCs. This also accords with our earlier observations,which showed that reduced expression of 14-3-3γhad a negative impact on the osteoblastic transdifferentiation ofNIH3T3-L1 cells. Taken together, these findings suggest a regulatoryrole for 14-3-3γin hASC differentiation to the osteogenic lineage.